Coral Reef Club, Barbados - West Nyack; Dexter Press, manufacturer (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2024)
This is an aerial view of the Coral Reef Club in Barbados. The most visible architectural features of the building are the roof work, the doors and the windows. The hotel is situated on the beach. Several persons are sitting on the beach chairs under the umbrellas. Two cars are parked under the hotel’s porch. This is an undivided back postcard. Back of the Postcard; Dear Uncle Aunty. Just a line. Having a good time. Weather been good, very hot. We will be on our way back home in a few days time. Bringing back the good weather with us. ? for now, Florence. Adressed to : Mr & Mrs J ?, 20 Hurstdene Road, Castle Lane West, Bournemouth, ??, England Da Costa & Musson Ltd., Commission & General Merchants Insurance, Airways and Shipping Agents, Barbados, W.I. Postage Stamp is attached: Bridgetown, Barbados, Postage Stamp, 015, $1Crs, 231V71 H £8 (Handwritten in Pencil)
Landscape, Colour, 3 ½” x 5½”
Keywords: Architectural features; Beaches; Hotels; Roofs; Tourists; Tourism; Windows; Historic buildings; Doors